Delivery of siRNA to Ewing Sarcoma Tumor Xenografted on Mice, Using Hydrogenated Detonation Nanodiamonds: Treatment Efficacy and Tissue Distribution - Sandra Claveau; Émilie Nehlig; Sébastien Garcia-Argote; Sophie Feuillastre; Grégory Pieters; Hugues A. Girard; Jean-Charles Arnault; François Treussart; Jean-Rémi Bertrand (Nanomaterials, 2020)
Nanodiamonds of detonation origin are promising delivery agents of anti-cancer therapeutic compounds in a whole organism like mouse, owing to their versatile surface chemistry and ultra-small 5 nm average primary size compatible with natural elimination routes. However, to date, little is known about tissue distribution, elimination pathways and efficacy of nanodiamonds-based therapy in mice. In this report, we studied the capacity of cationic hydrogenated detonation nanodiamonds to carry active small interfering RNA (siRNA) in a mice model of Ewing sarcoma, a bone cancer of young adults due in the vast majority to the EWS-FLI1 junction oncogene. Replacing hydrogen gas by its radioactive analog tritium gas led to the formation of labeled nanodiamonds and allowed us to investigate their distribution throughout mouse organs and their excretion in urine and feces. We also demonstrated that siRNA directed against EWS-FLI1 inhibited this oncogene expression in tumor xenografted on mice. This work is a significant step to establish cationic hydrogenated detonation nanodiamond as an effective agent for in vivo delivery of active siRNA.